Rebound : split 7' - Hero Dishonest; Rebound (yhtye); Combat Rock Industry ([Helsinki] : If Society ; [Riihimäki] : Combat Rock Industry, 2002)
6 kappaletta.
Stupid fucking world -- Girls -- The sword of righteousness is buried in my backyard -- Fallen with you -- Injection -- Another piece in the puzzle.
Kappaleiden tekijätietoja ei mainita.
A-puoli: Hero Dishonest (yhtye).
B-puoli: Rebound (yhtye).
Puuttuu JYKin kokoelmasta
Keywords: Hero Dishonest -- EP:t.; Rebound (yhtye) -- EP:t.; punk rock